KEPEMIMPINAN TRANSFORMATIF BERBASIS NILAI DALAM MANAJEMEN PERUBAHAN SUMBER DAYA MANUSIA LEMBAGA DAKWAH DI ERA DISRUPSI DIGITAL - Ekki Suryana Zaen; Cecep Castrawijaya (Raqib: Jurnal Studi Islam, 2026)
The era of digital disruption has posed structural challenges for Islamic da'wah institutions in Indonesia, not only in terms of technology, but also in human resource (HR) governance and leadership models. This study aims to analyze the role of value-based transformative leadership in managing HR change within da'wah institutions amid digital disruption. Using a qualitative approach through library research and content analysis, this study explores the relationship between leadership models, HR transformation dynamics, and the integration of spiritual values in mission-driven organizations. The findings indicate that transformative leadership rooted in Islamic values, such as amanah (trustworthiness), shura (deliberation), and maslahah (common good), functions as a more systematic, adaptive, and sustainable catalyst for HR change than conventional leadership models. This study also finds that resistance to change in da'wah institutions is multidimensional, encompassing cultural, psychological, and ideological aspects. As its novelty, this study proposes a new conceptual model termed Value-Based Transformational Leadership (VBTL), which synthetically integrates spiritual, managerial, and digital dimensions. This model is intended to serve as a theoretical-practical framework for developing da'wah institution management that is responsive to digital dynamics while preserving its value identity.